Pengaruh Pajak Daerah Dan Retribusi Daerah Terhadap Pad Dengan Jumlah Penduduk Sebagai Variabel Moderasi - Chintya Anggun Lestari; Slamet Riyadi (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2024)
This study aims to determine and analyze the effect of regional tax revenues and regional retribution on local origional income with population as a moderation variable in the Lamongan Regency Government in 2015-2022. This research is included in quantitative research with the type of data used, namely secondary data obtained from the Badan Pemeriksa Keuangan (BPK) of East Java Province Representative and Badan Pusat Statistik (BPS) of Lamongan Regency. The population in this study is all reports containing the types of regional taxes, regional retribution, local original income and population of Lamongan Regency for 2015-2022 totalling 334 data. The sampling technique is purposive sampling with the final number of samples used which is 240 data. The data analysis method used is descriptive data analysis with the help of SmartPLS statistical tools. The results of this study show that regional taxes and regional retribution have a positive and significant effect on local original income, population is able to moderate the relationship of regional taxes to local original income with weak categories, and population is able to moderate the relationship of regional retribution to local original income with strong categories.